Nonadiabatic breakdown and pairing in high-Tc compounds: General Aspects
The electron-phonon interaction plays a fundamental role on the superconducting and normal state properties of all the high-Tc materials, from cuprates to fullerenes. Another common element of these compounds is in addition the extremely small Fermi energy EF, which is comparable with the range wph of the phonon frequencies. In the situation the adiabatic principle wph/EF